(untitled) (International Journal of Engineering and Computer Science, 2016)
Now a day, social sites are getting popularity in every age person because of its easy install, interface, access and update. In future, there are two biggest challenges with respect to digitalization. First is a usage of internet and second is spending time in using internet. After spending maximum time, still there is question in mind that is user analyzing, learning, getting knowledge from received message by any means. In general, there is no creativity and just user are wasting time, money of their as well as others. In this paper, this challenges and objectives: utilization and productivity, has been highlighted, studied and discussed.